2021
DOI: 10.25259/sni_605_2021
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric brain abscess – etiology, management challenges and outcome in Lagos Nigeria

Abstract: Background: Brain abscess in children is a neurosurgical emergency with potentially catastrophic outcome despite the advances made in neuroimaging techniques and antibiotic therapy. Symptoms are nonspecific and may vary with the child’s age, location, size, numbers and stage of abscess, and the primary source of infection. Treatment is usually with broad-spectrum antibiotics in combination and surgical evacuation in most cases or antibiotics alone in selected cases with clear-cut indications. This study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…9 In another study conducted by Ahmad S et al, significant residual abscesses in 17 (17%) of the patients required re-aspiration. 10 This slightly increased rate of re-aspiration in our study might be a result of the patient's late presentation and poor preoperative health, which prevents the antibiotic from entering the abscess sac while the abscess is in the late capsule stage.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…9 In another study conducted by Ahmad S et al, significant residual abscesses in 17 (17%) of the patients required re-aspiration. 10 This slightly increased rate of re-aspiration in our study might be a result of the patient's late presentation and poor preoperative health, which prevents the antibiotic from entering the abscess sac while the abscess is in the late capsule stage.…”
Section: Discussionmentioning
confidence: 68%
“…12 In another study conducted by Ahmad et al, the parietal region was the most frequently affected in 44 patients (44%) followed by the frontal in 33(33%), temporal in 13 (13%), and occipital regions in 10 (10%). 10 This may be attributed to the hematogenous source being the most common route of infection and the internal carotid artery's role in providing 80% of the blood supply to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous trans-fontanelle subdural aspiration of intracranial subdural and intra-axial pus has been documented; however, this should be employed with great caution. [ 7 13 15 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…The causative organisms correlate with the age of the patient and the primary source of infection. [ 19 ] In our series, the positive cultures were from patients who had SDE complicating previous neurosurgical procedures. One yielded methicillin-resistant S. aureus and the other, P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of causative microorganisms depends on factors such as age, immunocompetence, location, social income, culture, and other essential factors when approaching a patient suspected of having a brain abscess. Several studies since the 20th century have shown that the main microorganisms are Streptococcus, Staphylococcus, and gram-negative enteric bacteria [2,[8][9][10]. The location of the brain abscess can be intracranial or extracranial, such as subdural or epidural, and is essential in eligible treatment, such as antibiotics alone or with neurosurgery [8,9].…”
Section: Introductionmentioning
confidence: 99%